Patient‐reported quality‐of‐life outcomes after de‐escalated chemoradiation for human papillomavirus‐positive oropharyngeal carcinoma: Findings from a phase 2 trial. Issue 3 (17th October 2017) - Hegde, John V.; Shaverdian, Narek; Daly, Megan E.; Felix, Carol; Wong, Deborah L.; Rosove, Michael H.; Garst, Jordan H.; Wang, Pin‐Chieh; Veruttipong, Darlene; Rao, Shyam; Fragoso, Ruben C.; Riess, Jonathan W.; et al.
Abstract : BACKGROUND: The current study represents a subset analysis of quality‐of‐life (QOL) outcomes among patients treated on a phase 2 trial of de‐escalated chemoradiation for human papillomavirus (HPV)‐associated oropharyngeal cancer. METHODS: Eligibility included newly diagnosed, (American Joint Committee on Cancer, 7th edition) stage III or IV oropharyngeal squamous cell carcinoma, p16 positivity, age ≥ 18 years, and a Zubrod performance status of 0 to 1. Treatment was induction paclitaxel at a dose of 175 mg/m 2 and carboplatin at an area under the curve of 6 for 2 cycles followed by response‐adapted, dose‐reduced radiation of 54 Gy or 60 Gy with weekly concurrent paclitaxel at a dose of 30 mg/m 2 . The University of Washington Quality of Life (UW‐QOL) and the Functional Assessment of Cancer Therapy‐Head and Neck questionnaires were used to assess patient‐reported QOL as a secondary endpoint. RESULTS: A total of 45 patients were registered, 40 of whom completed QOL surveys and were evaluable. Nadirs for overall UW‐QOL and Functional Assessment of Cancer Therapy‐Head and Neck scores were reached at 4 weeks after treatment but returned to baseline at 3 months. Nearly all functional indices returned to baseline levels by 6 to 9 months. The mean overall UW‐QOL score was 71.6 at baseline compared with 70.8, 73.0, 83.3, and 81.1, respectively, at 3 months, 6 months, 1 year, and 2 years after therapy. The percentage of patients rating their overall QOL as "very good" or "outstanding" at 6 months, 1 year, and 2 years using the UW‐QOL was 50%, 77%, and 84%, respectively. CONCLUSIONS: This de‐escalation regimen achieved QOL outcomes that were favorable compared with historical controls. These results serve as powerful evidence that ongoing de‐escalation efforts lead to tangible gains in function and QOL. Cancer 2018;124:521‐9. © 2017 American Cancer Society . Abstract : This subset analysis of quality of life among patients treated on a phase 2 trial of de‐escalated chemoradiation for human papillomavirus‐associated squamous cell carcinoma of the oropharynx demonstrates favorable outcomes compared with historical controls. These results serve as powerful evidence that ongoing de‐escalation efforts lead to tangible gains in function and quality of life.